Ten‐year experience of protocol‐based management of small‐for‐gestational‐age fetuses: perinatal outcome in late‐pregnancy cases diagnosed after 32 weeks. (2nd January 2021) - Meler, E.; Mazarico, E.; Eixarch, E.; Gonzalez, A.; Peguero, A.; Martinez, J.; Boada, D.; Vellvé, K.; Gomez‐Roig, M. D.; Gratacós, E.; Figueras, F.
ABSTRACT: Objective: To report our 10‐year experience of protocol‐based management of small‐for‐gestational‐age (SGA) fetuses, based on standardized clinical and Doppler criteria, in late‐pregnancy cases. Methods: A retrospective cohort was constructed of consecutive singleton pregnancies referred for late‐onset (> 32 weeks) SGA (defined as estimated fetal weight (EFW) < 10 th centile) that were classified as fetal growth restriction (FGR) or low‐risk SGA, based on the severity of smallness (EFW < 3 rd centile) and the presence of Doppler abnormalities (uterine artery pulsatility index (UtA‐PI) ≥ 95 th centile or cerebroplacental ratio (CPR) < 5 th centile). Low‐risk SGA pregnancies were followed at 2‐week intervals and delivered electively at 40 weeks. FGR pregnancies were followed at 1‐week intervals, or more frequently if there were signs of fetal deterioration, and were delivered electively after 37 + 0 weeks' gestation. The occurrence of stillbirth and composite adverse outcome (CAO; defined as neonatal death, metabolic acidosis, need for endotracheal intubation or need for admission to the neonatal intensive care unit) was analyzed in low‐risk SGA and FGR pregnancies. Results: A total of 1197 pregnancies with EFW < 10 th centile were identified and classified at diagnosis as low‐risk SGA ( n = 619; 51.7%) or FGR ( n = 578; 48.3%). Of these, 160 were delivered before 37 weeks' gestation; for obstetric reasons in 93 (58.1%) cases, severe pre‐eclampsia in 33 (20.6%), FGR with severe hypoxia in 47 (29.4%) and stillbirth in four (2.5%) (indications are non‐exclusive). During follow‐up, 52/574 (9.1%) low‐risk SGA pregnancies were reclassified as FGR, whereas 22/463 (4.8%) FGR pregnancies were reclassified as low‐risk SGA. Overall, there were no stillbirths in the low‐risk SGA group and four in the FGR group, all of which occurred before 37 weeks. There were no instances of neonatal death in pregnancies delivered ≥ 37 weeks. The risk of CAO was higher in those meeting antenatal criteria for FGR at 37 weeks than in those classified as low‐risk SGA (32/493 (6.5%) vs 15/544 (2.8%); odds ratio, 2.5 (95% CI, 1.3–4.6)). In FGR pregnancies, the adjusted odds ratio (95% CI) for CAO was 6.3 (1.8–21.1) in those with EFW < 3 rd centile, while it was 3.2 (1.5–6.8) and 4.2 (1.9–8.9) in those with UtA‐PI ≥ 95 th centile and CPR < 5 th centile, respectively, as compared to FGR pregnancies without each of these criteria. Conclusion: Protocol‐based risk stratification with different management and monitoring schemes for late pregnancy with a suspected SGA baby, based on clinical and Doppler criteria, enables identification and tailored assessment of high‐risk FGR, while allowing expectant management with safe perinatal outcome for low‐risk SGA fetuses. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.